Supercritical fluid cleaning : fundamentals, technology and applications - McHardy, John; Sawan, Samuel P. (Materials science and process technology series., 1998)
Addresses the application of cleaning in reference to extraction and purification processes (in the petrochemical, food and pharmaceuticals industries), provides a roadmap for readers who want to know whether SCF technology can meet their own processing and cleaning needs, and discusses solutions for those striving to balance the requirements for a clean product and a clean environment. Subject matter is directed toward scientists and engineers in all specialties ranging from materials and polymer sciences to chemistry and physics, and toward those developing new processes for other applications.